The Intradialytic Exercise, Cognitive Behavioral Therapy, and Deep Breath Relaxation for QOL In Hemodialysis Patients: Systematic Review - Akhmad Huda; Faridah Mohd Said; Jayasree S Kanathasan; Sofyan Hadi Hasibuan; Firnanda Erindia; Kushariyadi Kushariyadi (Universitas Jember, 2024)
Chronic kidney disease (CKD) patients undergoing continuous hemodialysis (HD) experience decreased daily physical activity, lower tolerance to exercise and poorer health-related quality of life. Thus, HD patients need interventions that focus on their physical and psychological characteristics to improve their quality of life. This study aims to discuss the effectiveness of intradialytic exercise, cognitive behavior therapy and deep breath relaxation in improving the quality of life of hemodialysis patients. The study used a systematic literature review design to identify articles on intradialytic exercise, cognitive behavior therapy and deep breath relaxation from 2019-2023 was obtained from PubMed, ScienceDirect and Google Scholar. Seven studies found that intradialytic exercise enhances CKD patients' quality of life during hemodialysis. Four studies noted cognitive behavioral therapy's positive impact on physiological aspects, enhancing patients’ well-being. Additionally, six studies observed deep breath relaxation's beneficial effects on physiological parameters, ultimately enhancing patients' quality of life during hemodialysis. Intradialytic exercise, cognitive behavior therapy and deep breath relaxation are effective in improving the quality of life of hemodialysis patients. Furthermore, these three interventions helped accelerate the medical approach to chronic kidney disease.